Ten-year predictors of major adverse cardiovascular events in patients without angina - Preesha Premsagar; Colleen Aldous; Tonya Esterhuizen (South African Family Practice, 2023)
Background: Longstanding cardiovascular risk factors cause major adverse cardiovascular events (MACE). Major adverse cardiovascular events prediction may improve outcomes. The aim was to evaluate the ten-year predictors of MACE in patients without angina.